When love blooms - Hatcher, Robin Lee (Zondervan, 2008)
Emily wanted to be more than just a society wife. She came to the Idaho high country looking to make a difference. Gavin knows she would never make it in the rugged high country... but his resistance makes her more determined to prove herself.